Association between early cerebral oxygenation and neurodevelopmental impairment or death in premature infants - Katheria, Anup C. (J Perinatol, 2021)
OBJECTIVE: To assess the relationship between cerebral oxygenation in the first 72 h of life and neurodevelopmental impairment (NDI) at 2 years corrected age in former premature infants. STUDY DESIGN: Prospective observational cohort study of 127 infants <32 weeks GA at birth with cerebral oxygenation monitoring using NIRS in the first 72 h of life. RESULTS: Using a threshold cutoff for cerebral hypoxia, infants with NDI or death had increased duration of hypoxia (4 vs 2.3%, p = 0.001), which was more pronounced in the 23–27 week subgroup (7.6 vs 3.2%, p < 0.001). Individual generalized estimating equations to adjust for repeated measures were modeled in this subgroup for the physiologic parameters including StO(2). StO(2) < 67% was a predictor for death or NDI (OR 2.75, 95% CI 1.006, 7.5132, p = 0.049). CONCLUSION: An increased duration of cerebral hypoxia is associated with NDI or death in infants born <32 weeks GA.